Violence and the COVID-19 pandemic in the mega-city: a changing geography of homicide in Greater Buenos Aires, Argentina? - Leveau, Carlos Marcelo (2025)
We analyzed the geographic changes in homicide following the onset of the pandemic in Greater Buenos Aires. For each homicide, the month and census tract in which the death occurred were used. The Bernoulli model was used to detect both the spatial concentration and the spatio-temporal concentration of homicides during the each of the years 2019 and 2020. With respect to low homicide risk clusters, high homicide risk clusters tended to be located in areas of high structural poverty in both years. During 2020, there was an overall similarity to the geographic pattern found in 2019. However, there were some differences in high-risk clusters between both years. Compared to 2019, a lower spatial diffusion of homicides was apparent during 2020. We found no evidence of abrupt changes in the geography of homicide with the onset of the pandemic.